Women’s experience of divorce. Acta biomedica scientifica - E. V. Tikhomirova; A. G. Samokhvalova; S. A. Khazova; M. V. Saporovskaia; D. A. Chicherina (Acta Biomedica Scientifica, 2022)
The article is devoted to the problem of studying the experience of women going through the situation of divorce at different stages of the divorce and post-divorce period.Methods. The study was carried out at the intersection of idiographic and nomothetic approaches. At the first stage, the specifics of the experience of experiencing divorce in the online space are described, revealed through an interpretive-phenomenological analysis of the content of a closed Internet forum (n = 297). On the second – the specifics of emotional perception, cognitive assessment and coping with the situation of divorce, depending on the post-divorce experience (n = 50).Results. The experience of divorce by women is accompanied by ambivalent emotions, activates the understanding of the situation and coping with it. Online communication is an effective strategy focused on getting support, self-change, designing the future, allowing you to experience a sense of community in a life situation while maintaining psychological safety. The assessment of the divorce situation and coping strategies are specific: women who have gone through a divorce less than 3 years ago are more likely to seek social support; from 3 to 10 years – prefer the strategy of “flight-avoidance”; more than 10 years ago – “positive revaluation”. Conclusion. The experience of women experiencing the situation of divorce, including emotional, cognitive and conative components, is specific depending on the stage of the divorce and post-divorce period. An effective mechanism for shaping the experience of experiencing a divorce is network communication in a closed group of people who have similar problems.